Pengaruh berkumur larutan probiotik terhadap peningkatan pH saliva pada anak-anak - Febriani Claudia Sanulo Zebua; Wilvia Wilvia; Idamawati Nababan; Suci Erawati (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2019)
Saliva is a complex body fluid and plays an important role in the biological process of the oral cavity. If the saliva volume decreases, the pH of the oral cavity also decreases. A decrease in salivary pH can cause tooth demineralization, growth of acidogenic bacteria such as Streptococcus mutans and Lactobacillus and dental caries. One way to maintain microbial balance and increase salivary secretion is a probiotic solution (yogurt). This study aims to determine the effect of rinsing probiotic solution on increasing salivary pH. This type of research is experimental with pre and post test group design. The samples in this study were children of the Terima Kasih Orphanage, which numbered 35 people and had met the inclusion criteria. The results showed that the mean salivary pH before rinsing probiotic solution was 4.74 ± 0.6151 and after 6.63 ± 0.6029. From the test results obtained a significance value of p = 0,000 (p <0.05) which means that there is a significant effect of gargling with probiotic solutions on increasing salivary pH in children of the Terima Kasih Orphanage in Medan City in Years 2019. Thus, the conclusion of this study is Probiotic solutions proved effective in increasing the salivary pH.